Professional'nyj basketbol v Rossii: problemy i osobennosti sovremennogo etapa razvitija - Ganiev, R. G.; Mazurina, A. V.; Likhachev, O. E. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The admission of the professional athletes to all international competitions has led to the radical changes in their professionalization and commercialization, which has contributed to the leaping growth of the sports results. The dominance of international professional sporting competitions over the national ones is explained by their high popularity, demand from the spectators and financial gain (profitability) for the organizers and athletes. As a result of these innovations, the high level of professional sports development has become a prerequisite for achieving high sporting results in the international sporting arena. Moreover, the professional sports leagues have begun to cramp and reduce the status of most sports competitions held by the international and national sports federations, involving the kinds in sport, which have not been able to compete with the professional athletes and their status has declined significantly. Cases of refusal of the leading professional athletes to participate in even the largest and most prestigious international competitions, held by the non-professional leagues, have increased. Firstly, this is due to a very busy, and intense stressful calendar of the professional competitions and, secondly, to the reduction of the time required for the rest and recovery of the professional athletes after a busy competitive calendar, because most of these competitions are held during the transitional period of the cycle year, i.e. during the vacations and rest of the professional athletes. The proposed article is an attempt to analyze some of them: the article attempts to address the problems of professionalization and commercialization, as well as changes in the legislative framework, financial and organizational support necessary for solving the problems of professionalization of sports games and the transition of the system of training sports reserves for professional sports mainly on the commercial basis in the country. The complexity of the process of transitioning the functioning of the professional sports clubs and the system of training sports reserves on the commercial, professional basis in our country is analyzed, being explained with the lack of necessary information about the organization and experience of functioning of the professional leagues, sports professional clubs for sports games in foreign professional sports.